Research Status of Mesenchymal Stem Cells in Liver Transplantation. Issue 12 (December 2019) - You, Yu; Wen, Di-guang; Gong, Jian-ping; Liu, Zuo-jin
Liver transplantation has been deemed the best choice for end-stage liver disease patients but immune rejection after surgery is still a serious problem. Patients have to take immunosuppressive drugs for a long time after liver transplantation, and this often leads to many side effects. Mesenchymal stem cells (MSCs) gradually became of interest to researchers because of their powerful immunomodulatory effects. In the past, a large number of in vitro and in vivo studies have demonstrated the great potential of MSCs for participation in posttransplant immunomodulation. In addition, MSCs also have properties that may potentially benefit patients undergoing liver transplantation. This article aims to provide an overview of the current understanding of the immunomodulation achieved by the application of MSCs in liver transplantation, to discuss the problems that may be encountered when using MSCs in clinical practice, and to describe some of the underlying capabilities of MSCs in liver transplantation. Cell–cell contact, soluble molecules, and exosomes have been suggested to be critical approaches to MSCs' immunoregulation in vitro; however, the exact mechanism, especially in vivo, is still unclear. In recent years, the clinical safety of MSCs has been proven by a series of clinical trials. The obstacles to the clinical application of MSCs are decreasing, but large sample clinical trials involving MSCs are still needed to further study their clinical effects.